Separation times analysis of unsteady magnetohydrodynamics mixed convective flow past a Sphere - Mohammad, Nurul Farahain; Mohd Kasim, Abdul Rahman; Ali, Anati; Shafie, Sharidan (American Institute of Physics, 2014)
The separation of flow for unsteady problem occurred on some events even though the fluid is laminar flow. In this paper, the times when then boundary layer flow start to separate from flowing at the surface of a sphere are investigated in the presence of magnetic field. It is also considered that the fluid flow and heat transfer are governed by both buoyancy and external forces. In order to solve this problem, the dimensional equations that govern the fluid flow and heat transfer are transformed into dimensionless equations by using appropriate dimensionless variables. The stream functions are introduced to connect and thus having a function that can represent velocities. Similarity variables are used to deduce the dimensionless governing equations into a system of nonlinear partial differential equations. This system of equations is solved numerically by using numerical scheme known as the Keller-Box method. The numerical results obtained are presented in tabular form and analyzed.